2005
DOI: 10.1111/j.1538-7836.2005.01290.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of LMWH in pregnancies at risk: new evidence or perception?

Abstract: The debate goes on. Antithrombotic prophylaxis for women with thrombophilia and pregnancy complications is controversially discussed. In the October 2003 issue of the Journal of Thrombosis and Haemostasis, Middeldorp argued against the implementation of a Ôpotential harmful therapyÕ in women with hereditary thrombophilia and a history of recurrent pregnancy loss [1]. In the same issue, Brenner argued in favor of a heparin prophylaxis, based on the results of the limited number of studies available [2]. A forum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Documentation of thrombophilic risk factors in women with pregnancy complications may have significant therapeutic implications as a number of clinical studies have demonstrated the potential efficacy of prophylaxis with low molecular weight heparin (LMWH) in these settings [10,11]. While interpretation of the results of these studies arose some debate [12–22], it is clear that the field of thrombophilia and pregnancy complications continues to be in the focus of medical research and clinical practice.…”
mentioning
confidence: 99%
“…Documentation of thrombophilic risk factors in women with pregnancy complications may have significant therapeutic implications as a number of clinical studies have demonstrated the potential efficacy of prophylaxis with low molecular weight heparin (LMWH) in these settings [10,11]. While interpretation of the results of these studies arose some debate [12–22], it is clear that the field of thrombophilia and pregnancy complications continues to be in the focus of medical research and clinical practice.…”
mentioning
confidence: 99%